Leaving Marks and Names on the Land: The Deeds of Tama Ki Te Rangi, Tamatea-Pōkai-Whenua, Te Rakiwhakaputa and Rākaihautū - Lloyd Carpenter (Landscape Review, 2022)
Stories of first explorations and the naming of landmarks, boundaries and resources by a renowned tipuna (ancestor) feature in most Māori pūrākau (oral traditions). The first explorer sets out captaining their great waka (ocean-going canoe), fighting battles with monsters or other explorers, enduring hardship to traverse the land and discover, name or create geographical features on their journey. In this way, the intrepid pioneer declares and defines the boundaries of the takiwā (area of responsibility) of their iwi (tribe), metaphorically throwing a korowai (cloak) of their mana (prestige or honour) and responsibility over the new whenua (land), embedding their nomenclature, collective tribal mauri (spirituality), traditions and whakapapa (genealogies) into the lands they anticipate their peoples will settle. Naming confers the status of mana whenua (local people), but in the Māori (Indigenous New Zealander) world, it confers much more than that. Naming, especially when done by a prominent leader or explorer, is the step that sees the recent settlers accept the role of kaitiaki (guardian) for the environment of their new home, as well as the resources it can produce. In this paper, I examine the deeds of the explorers of the past, comparing the kaupapa (methodology) of name-giving with the arbitrary nomenclature systems of settler surveyors and explorers in the nineteenth century, revealing the stories behind each original name and offering reasons for recognising them today.